2013
DOI: 10.1007/s12298-013-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of ISSR, DAMD and SCoT markers for evaluation of genetic diversity and conservation of landrace chickpea (Cicer arietinum L.) genotypes collected from north-west of Iran

Abstract: Morphological traits and three molecular markers techniques: start codon targeted (SCoT), inter-simple sequence repeat (ISSR) and directly amplified minisatellite DNA (DAMD) markers were compared for fingerprinting of 40 landraces chickpea genotypes collected from different geographical locations of north-west of Iran. Variance analysis of ten measured morphological traits showed significant differences existed between genotypes. Cluster analysis based on morphological traits, divided genotypes in three distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 27 publications
9
39
0
Order By: Relevance
“…Although the polymorphism rate for the markers was relatively similar, we anticipate that the source of detected diversity differs, as the markers target different regions of the genome (Pakseresht et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the polymorphism rate for the markers was relatively similar, we anticipate that the source of detected diversity differs, as the markers target different regions of the genome (Pakseresht et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors also reported that these marker techniques were able to provide more reliable diversity information compare to RAPD or ISSR techniques (Amirmoradi et al 2012;Li et al 2013;Poczai et al 2013) and are useful as tools for studying the genetic diversity of different plant germplasm. There have been previous reports on clustering of genotypes using gene-based molecular markers in potato (Gorji et al 2011), chickpea (Pakseresht et al 2013;Hajibarat et al 2015), ramie (Satia et al 2015), and wheat (Hamidi et al 2014). In comparison with those studies, we found that the average polymorphism rate for SCoT and CDDP markers in Iranian durum wheat landraces were relatively high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of start codon targeted, directly amplified minisatellite DNA and ISSR markers was quite similar in finger printing of genotypes and might be employed to identify polymorphism for genotypes of chick pea (Cicer arietinum) [18].…”
Section: Genetic Profiling (Dna Fingerprinting)mentioning
confidence: 99%